Peran Tenaga Pendidik dalam Meningkatkan Kreativitas Siswa di Era Kurikulum Merdeka - Rina Inayah (Universitas Maritim AMNI Semarang, 2024)
As educators, you should have ideas for increasing creativity for students, and teaching students to always learn skillfully, creatively and independently. Currently, almost all of Indonesia uses the Merdeka curriculum, where the Merdeka curriculum also demands the active role of teaching staff in increasing creativity for students in the learning process both in the classroom and outside the classroom. The aim of the article is expected to provide a reference for students now and in the future. The method used in this article uses a descriptive qualitative method based on the data needed and received. From the analysis at SMP NEGERI 2 SERANG CITY regarding the role of teachers in increasing student creativity in the current era of the independent curriculum, it can be said to be good.